Bipolar Expeditions : Mania and Depression in American Culture - Martin, Emily (Book collections on Project MUSE., 2009)
Manic behavior holds an undeniable fascination in American culture today. It fuels the plots of best-selling novels and the imagery of MTV videos, is acknowledged as the driving force for successful entrepreneurs like Ted Turner, and is celebrated as the source of the creativity of artists like Vincent Van Gogh and movie stars like Robin Williams. Bipolar Expeditions seeks to understand mania's appeal and how it weighs on the lives of Americans diagnosed with manic depression. Anthropologist Emily Martin guides us into the fascinating and sometimes disturbing worlds of mental-health support gr.